2019
DOI: 10.1002/asia.201900745
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Conversion of 2‐(Alkynonyl)Alkynylbenzenes to Isocoumarins by a Retro‐Favorskii‐like Degradation

Abstract: We report the discovery of an anomalous reaction of 2‐(alkynonyl)alkynylbenzenes under AgI catalysis for the selective formation of isocoumarins. This reaction is previously undocumented for 2‐(alkynonyl)alkynylbenzenes in terms of the reaction mechanism and the product formed. Water (H2O18) labeling studies suggested a possible mechanistic pathway in which the initial formation of a pyrylium ion is followed by hydrative dealkynylation, that is, water incorporation and alkyne expulsion, similar to a retro‐Favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Baire et al. in 2019 reported the synthesis of isocoumarins from 2‐(alk‐2‐yn‐1‐onyl)‐1‐alkynylbenzenes 272 in the presence of Ag(I) [224] . Utilising 272 in the present study in 2022, Baire's group found an inseparable mixture of two new compounds instead of isocoumarin.…”
Section: Introductionmentioning
confidence: 51%
“…Baire et al. in 2019 reported the synthesis of isocoumarins from 2‐(alk‐2‐yn‐1‐onyl)‐1‐alkynylbenzenes 272 in the presence of Ag(I) [224] . Utilising 272 in the present study in 2022, Baire's group found an inseparable mixture of two new compounds instead of isocoumarin.…”
Section: Introductionmentioning
confidence: 51%
“…AgOTf‐catalyzed synthesis of isocoumarins 125 from 2‐(alkynonyl)alkynylbenzenes 124 in toluene at 0 °C to room temperature condition was reported (Scheme 69). [74] The protocol opens up a new pathway for isocoumarin synthesis and involves a retro‐Favorski mode of mechanism through a pyrylium ion intermediate 126 formation. The plausible mechanistic pathway is also depicted (Scheme 70 ) .…”
Section: Six Membered Heterocycles With One Heteroatommentioning
confidence: 99%
“…There are two species in China, which were widely planted in Fujian, Guangxi, Guangdong and Hainan Province of China as ornamental plants [2] . The flowers of several Plumeria species can be used as tea, with the effects of clearing heat, promoting diuresis, and relieving summer heat [3] . Previous chemical investigations on the genus Plumeria have reported many natural products including iridoids, [6–8] flavones, [8,9] triterpenoids, [7,8,10–12] and ferulic acids [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[2] The flowers of several Plumeria species can be used as tea, with the effects of clearing heat, promoting diuresis, and relieving summer heat. [3] Previous chemical investigations on the genus Plumeria have reported many natural products including iridoids, [6][7][8] flavones, [8,9] triterpenoids, [7,8,[10][11][12] and ferulic acids. [13] Among these natural products, iridoids are considered as the main characteristic constituents in the genus Plumeria, which generally contains a 5/5/6 three-ring system with an aglycone.…”
Section: Introductionmentioning
confidence: 99%